2018
DOI: 10.1080/10428194.2018.1433297
|View full text |Cite
|
Sign up to set email alerts
|

A real-world study of clofarabine and cytarabine combination therapy for patients with acute myeloid leukemia

Abstract: Clofarabine and cytarabine (Clo + Ara-C) combinations have efficacy in treatment of acute myeloid leukemia (AML). We retrospectively analyzed clinical outcomes of 71 AML patients receiving Clo + Ara-C regimens at the University of Minnesota from 2011 to 2016: 44 patients (62%) had newly diagnosed AML and 27 patients (38%) had relapsed/refractory AML. The median age of patients was 69 years (interquartile range [IQR], 63-75 years). Nearly 60% of the patients had secondary AML, and about half of patients had adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…At our center, we use MEC (mitoxantrone, etoposide, and cytarabine for 5 days) 12 for fit patients and Clo/Ara-C (clofarabine for 5 days and low-dose cytarabine for 10 days) 13 for the less fit. The frequency and severity of mucositis with MEC or Clo/Ara-C are comparable to 7 + 3 14,15 . There are several standard chemotherapy induction protocols for ALL, all based on multi-agent regimens with varying risks of mucotoxicty.…”
Section: Methodsmentioning
confidence: 86%
“…At our center, we use MEC (mitoxantrone, etoposide, and cytarabine for 5 days) 12 for fit patients and Clo/Ara-C (clofarabine for 5 days and low-dose cytarabine for 10 days) 13 for the less fit. The frequency and severity of mucositis with MEC or Clo/Ara-C are comparable to 7 + 3 14,15 . There are several standard chemotherapy induction protocols for ALL, all based on multi-agent regimens with varying risks of mucotoxicty.…”
Section: Methodsmentioning
confidence: 86%
“…Clofarabine increases the anti-leukemic activity of cytarabine, 9 and recent studies have provided evidence in support of its effectiveness against both adult and pediatric AML. 10 12 , 21 , 22 Accordingly, Rubnitz et al 23 suggested that clofarabine could be used instead of anthracycline and etoposide during remission therapy for childhood AML, while Molteni et al 11 showed the potential of clofarabine-based chemotherapy as a bridge toward transplantation in patients with refractory/relapsed AML, especially after fludarabine-based salvage chemotherapy has been attempted.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] Studies have shown that clofarabine is effective against pediatric acute leukemia, 7,8 and that its combination with cytarabine was effective against AML. [9][10][11][12] Moreover, a few studies have indicated that combination chemotherapy involving clofarabine, cyclophosphamide, and etoposide was effective against relapsed/refractory acute lymphocytic leukemia (ALL) and AML. [13][14][15][16] However, the enrolled cases primarily involved ALL, due to the low number of registered AML cases.…”
Section: Introductionmentioning
confidence: 99%